Designing for action: An evaluation of Social Recipes in reducing food waste. Issue 100 (April 2017) - Lim, Veranika; Funk, Mathias; Marcenaro, Lucio; Regazzoni, Carlo; Rauterberg, Matthias
Abstract: Approximately, one-third to half of all food produced globally is wasted. In developed countries, roughly up to half of this food waste comes from consumers. In response to this, the UN has set goals to raise consumer awareness and reduce food waste by 50% before 2030. Our objective is to evaluate how emerging technologies could improve awareness in households. Inspired by future sensing possibilities, we envision a community-based social system that captures in-home food availability and waste patterns and uses this information to support awareness and sustainability. In this work, we describe an evaluation of a component that could be part of such a system. This component or concept, called Social Recipes, aims at encouraging food sharing by suggesting groups of related consumers recipes that are based on ingredients from different individuals or households. To evaluate Social Recipes, we conducted 3 user studies to see how it could raise awareness and reduce food waste and to suggest implications for its design. In the first two studies, we evaluated expected impacts of the concept. The third study was a home deployment, where Social Recipes were sent using technological probes for a more realistic experience. Here, we also evaluated it against the more common method of influence strategy in sustainability research that is restricted to feedback (i.e., eco-feedback). Our main findings showed that Social Recipes has raised awareness of in-home food availability and triggered food-related conversations among participants resulting in knowledge gain. However, Social Recipes alone was not perceived as effective in directly reducing food waste. And therefore, for the design of a community-based social system, we suggest another component to be added to the system that provides eco-feedback. This component was perceived as more effective in reducing food waste with impacts on awareness of waste generation and social surveillance. Overall, the aim of this work is to contribute to an understanding of how Social Recipes could impact consumers and how to design a community-based social (recipe) system that can be integrated in consumers daily activities for effective but pleasurable food waste prevention. Highlights: A new food sharing concept is explored (Social Recipes) against a more traditional method used in sustainability research. Social Recipe suggestions are expected to influence creativity and surprise, connectedness, coordination and knowledge. Social Recipe suggestions were perceived as having an impact on awareness and communication around food waste behavior. Social Recipe suggestions were evaluated as less effective and efficient than when eco-feedback was added as intervention. Eco-feedback with social comparison triggered competitiveness and surveillance. Whereas Social Recipes affected communication with regard to generating ideas of recipes and techniques to prevent waste.